EFEKTIVITAS MEDIA SOSIAL DALAM MENYAMPAIKAN PESAN DAKWAH PADA MASYARAKAT KELURAHAN MULYOJATI KECAMATAN METRO BARAT - Jamiah, Ririn; Rudini, Rudini; Elhany, Hemlan (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
Social media is a form of technological progress that is developing rapidly. Like Instagram and WhatsApp, which are currently owned by many Mulyojati Village people, especially teenagers. They use Instagram and WhatsApp as a medium for communication, to seek and obtain information and also to spread or convey da'wah messages.This study aims to find out how effective social media is in conveying da'wah messages to the people of Mulyojati Village, West Metro District. The method used in this study is (Fieldresearch) and is descriptive qualitative. The data sources used are primary and secondary data sources. Then the technique of data collection is done by observation, interviews and documentation. Data analysis in this study was qualitative in nature, namely collecting data, analyzing all data from interviews, observations written down in field notes, personal documents, official documents, photographs. Then do data reduction then do the abstract. Various effects of research results in the process of delivering da'wah messages, namely, First, Cognitive Effects, da'wah messages that are spread or conveyed via Instagram and WhatsApp can add insight and knowledge to the community. Second, Affective Effects, namely that only a few people apply the contents of da'wah messages in their daily lives. The third is the behavioral effect, namely that only a small portion of the community after observing the contents of the da'wah message then applies it in everyday life to practice it in others. Delivery of da'wah messages through social media to the people of Mulyojati Village is less effective. Because of the three effects in the process of delivering da'wah messages, only cognitive effects are mostly carried out by the community, especially teenagers. Most of the people of the Mulyojati Village, especially teenagers, use Instagram and WhatsApp to find and disseminate information related to Islamic da'wah messages.